Job satisfaction and job-hopping behaviour among employees of casual dining restaurant - Jules, Nathalie Joan; Ghazali, Hazrina; Othman, Mohhidin (Penerbit Universiti Teknologi MARA (UiTM) Malaysia, 2017)
Job hopping has been labelled as common practice among the labour workforce and this trend has been affecting many companies to review back their human resource strategy in order to reduce cost in high turnover and retain their employees within the organization. This paper aims to examine the relationship between job satisfaction and job-hopping behaviour mediated by affective commitment among employees working in the casual dining restaurant in Klang Valley area. With a total of 230 participants responded, data had been thorough screening of which only local workforce selected with an experience of working approximately one year from their employment life. Mediator affective commitment was also being examined in defining the mediation effect towards job hopping behaviour. Results from research findings indicated that job satisfaction does not predict job hopping behaviour and relationship are not significant. Job satisfaction has a positive relationship with affective commitment and is significant while affective commitment is weakly correlated to job hopping behaviour but not significant. This stipulates that even job satisfaction is a highly significance predictor towards affective commitment, both variables do not have strong causal effects to job hopping behaviour.